TOLAK UKUR PENILAIAN PENGGUNAAN DISKRESI OLEH POLISI DALAM PENEGAKAN HUKUM PIDANA - Abbas Said (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2012)
Basically, the law works by providing boundaries. In the context of law enforcement by the police, the constraints in the form of control over the police in freedom Protect the order or stop crime. But there is a different reality when police faced with a reality in which the law could not answer the problem. In this position the use of discretion by police do legal interpretation as a bridge between the law with social objectives. The question that arises then is used is not appropriate discretion and not in accordance with the purposes of the law itself. The benchmark police discretion based on common interests or the interests of society at the level of practice is still very abstract to be applied in the implementation of police discretion related to criminal law enforcement policy. Because the benchmark Criteria or public interest in the use of police discretion are still abstract, causing authorities use discretion in some cases criminal process misapplied. Keywords: Discretion, Police